Bureau Of Mines Development Of Titanium Production Technology - J. L. Henry (The National Institute for Occupational Safety and Health (NIOSH), 1987)
The development and status of technology for producing titanium from U.S. resource materials are summarized in this Bureau of Mines report. Commercially feasible processes and investigations of alternative procedures are reviewed in order to identify techniques that could make existing operations more effective or areas in which future research may lead to the development of new production methods. Procedures are described for producing concentrated titanium dioxide from starting materials such as sands, massive deposits, and mineral processing residues containing rutile, ilmenite, and perovskite; producing and purifying titanium tetrachloride from concentrated rutile, ilmenite, and titaniferous slags; reduction of titanium tetrachloride to titanium sponge metal using metallic magnesium or sodium; purifying and consolidating titanium sponge and scrap by arc melting or induction melting techniques; purifying sponge, scrap, and alloys by molten salt electrorefining; and electrowinning titanium from chloride salts.